Measurement of UK government output and productivity for the national accounts - Atkinson, A. B. (Statistical and Social Inquiry Society of Ireland, 2005)
The Atkinson Review was commissioned by the UK National Statistician in December 2003 to advance methodologies for the measurement of government output, productivity and associated price indices in the context of National Accounts. The report sets out the principles that should underpin future work in the measurement of government output and productivity. It makes specific proposals for improving output measures in Health, Education, Public Order and Social Protection. It also recommends broad approaches for developing the measurement of the output of public services that will improve the accuracy, coverage and interpretation of figures, with publication of methods and figures to ensure transparency and debate on ways of achieving further improvements. Sir Tony Atkinson, Warden of Nuffield College, Oxford, is one of the worlds leading economists and an expert in public economics.
Read before the Society, 14 April 2005
Keywords: Productivity; Public services; National accounts; 314.15